MEMBIDIK SISWA MENGENAL ARKEOLOGI - Hari Lelono (Berkala Arkeologi, 2006)
The era of reform in the world of politics has rolled on and is still in the process of learning for all Indonesian people to find the ideal format for implementing national development. Forms, ideal formats, are still limited to trials and aspirations that do not yet know when it will end. In exploring the identity, an interesting question, but it is quite outdated is, "why"? it continues to be a polemic for individual, group, religious and ethnic interests. The chaos should end in order to create an Indonesia that is peaceful and has an identity as the basis for a Indonesian personality with a characteristic plurality (diversity).